Implementation of Character Education Based on Local Ceremony in Nusalaut State Middle School (SMP) 2 - Sopacua, Fanry Julius; Sugiharto, DYP; Muhsin, Muhsin (Educational Management, 2020)
Local wisdom-based character education teaches students to always be attached to the concrete situations they face. Learning process will succeed if the teacher understands the insight of local wisdom itself in order to create learning that respects the diversity of regional culture. Schools are formal educational institutions that are effective in character building. The important thing that underlies character education in schools is that the inculcation of national character values will not succeed through the mere provision of information and doctrines. This study uses a qualitative approach with survey design. The purpose of this study is to analyze the implementation of character education in students at Nusalaut State Middle School 2. The research sample consisted of the principal and also the teachers at Nusalaut State Middle School 2. Data collection techniques using in-depth interviews, observation and documentation. The results showed that schools already have character standards in students, character education planning, religious cultural development activities in schools and the provision of supporting facilities. In the implementation process, teachers and school principals provide habituation and role models through daily or weekly activities such as religious and extracurricular activities. The evaluation of the implementation of character education is through the monitoring and supervision of daily activities that have been carried out by involving teachers and parents and finding solutions if there are obstacles in the implementation of character education. The impact of the implementation of character education based on local wisdom shows a positive response marked by the emergence of students religiosity, creativity and innovation, independence, courage to try, increasing insight and skills, responsibility and self-confidence, caring for nature conservation by doing good daily activities through religious and extracurricular activities.